Five ways to wellbeing at the zoo: improving human health and connection to nature - Rose, Paul; Riley, Lisa (Frontiers in Psychology, 2023)
Good mental and physical health go hand-in-hand when identifying factors that lead people to experience a better overall quality of life. A growing disconnect to the natural world is worsening the mental health of individuals in many societies. Numerous scientific publications have evidenced that being in nature and access to green and blue spaces positively impact upon humans’ physical and mental health. For many people, particularly those living in more urbanized areas, managed natural spaces and borrowed landscapes, such as those found in public parks, wildlife reserves and zoological gardens give the only opportunities for wider engagement with nature. Many zoos are designated green spaces and therefore human visitors can engage with native fauna and flora as well as exotic wild animals. This article reviews the UK Government’s “The Five Ways to Wellbeing” concept, applied to zoos and aquariums and thus suggests how zoos and aquariums can use this framework to promote positive nature-connectivity experiences for their visitors and promote good wellbeing. The Five Ways to Wellbeing are Connect, Be active, Take notice, Keep learning, and Give. We illustrate how zoos and aquariums could model their approaches to educational and engagement roles, as well as design initiatives to reach out to local communities via the Five Ways to Wellbeing concept. We show that many of the positive programs and works conducted by zoos and aquariums lend themselves to further engagement with the Five Ways to Wellbeing structure. By taking such a structured approach in the design, implementation and evaluation of their activities, zoos can expand their abilities in connecting humans with nature and further add value to their living collections of animals and plants. By including Wellbeing as a defined aim of the modern zoo, it will be clear to all of those involved in their work, visitors, workers, stakeholders, that zoos are working to promote, protect and preserve positive wellbeing outputs for humans and animals alike.